The Efficacy and Safety of Anlotinib Combined With PD-1 Antibody for Third-Line or Further-Line Treatment of Patients With Advanced Non-Small-Cell Lung Cancer - Zhai, Chongya; Zhang, Xiaoling; Ren, Lulu; You, Liangkun; Pan, Qin; Pan, Hongming; Han, Weidong (Frontiers in Oncology, 2021)
Background: Both Anlotinib and programmed death 1 (PD-1) monoclonal antibody (mAb) have been approved for the third line treatment of metastatic non-small cell lung cancer (NSCLC). However, the combination of these two standard therapies has not been investigated in third-line or further-line treatment of patients with advanced NSCLC. Methods: We reviewed 22 patients with NSCLC who received anlotinib combined with PD-1 mAb therapy from July 2018 to October 2019 at Sir Run Run Shaw Hospital. Based on the baseline characteristics, PD-L1 expression and EGFR mutation status, we retrospectively analyzed the efficacy and safety of this combination therapy by RESIST 1.1 and CTCAE 5.0. Results: The combination treatment of anlotinib and PD-1 mAb in 22 NSCLC patients gained a median PFS of 6.8 months and a median OS of 17.3 months. The disease control rate (DCR) was 90.9%, and the objective response rate (ORR) was 36.4%, where 1 (4.6%) patient achieved complete response (CR) and 7 (31.8%) patients achieved partial response (PR). The median time to response was 3.9 months, and the median duration of the response was 6.8 months. The common grade 1-2 adverse events were fatigue 10/22 (45.5%), decreased appetite 9/22 (40.9%), hypertension 10/22 (45.5%); the common grade 3-4 adverse events were hypertension 2/22 (9.1%) and mouth ulceration 2/22 (9.1%). Conclusion: Anlotinib combined with PD-1 mAb showed promising efficacy in third-line or further-line treatment of NSCLC, and its adverse effects is tolerable.